120 ASSOCIATION OF MICROSOMAL TRIGLYCERIDE TRANSFER PROTEIN −493G/T POLYMORPHISM WITH LIPID METABOLISM AND MICROVASCULAR COMPLICATIONS IN TYPE 2 DIABETIC PATIENTS. Issue 1 (1st January 2007) - Ershoff, B.; Durlach, V.; Durlach, A.; Movesayan, I.; Socquard, E.; Clavel, C.; Nazeyrollas, P.; Malloy, M.; Pullinger, C.; Kane, J.; Aouizerat, B.
Abstract : Background: Type 2 diabetes (T2D) affects over 15 million Americans, and the prevalence is rising precipitously. T2D patients are at risk for atherosclerosis and microvascular complications; identifying those at risk can lead to improved outcomes. Risk for complications due to dyslipidemia is modulated by genetic factors. Common variations in the microsomal triglyceride transfer protein (MTP −493G/T) and apolipoprotein B (apoB insertion/deletion [In/Del]) genes may modulate the risk for diabetic complications through their impact on lipid metabolism. Methods: As part of a longitudinal case-control study of T2D in a French population (401 cases, 113 controls, mean age 59.5 years at baseline, and 4.2-year mean follow-up) we examined the relationship between MTP −493G/T, apoB In/Del, lipoprotein parameters, and the prevalence of diabetic complications. Results: After adjusting for relevant covariates, MTP −493G/T was associated with T2D ( p = .032), lower apoB concentrations ( p = .024), triglycerides ( p = .047), total cholesterol ( p = .049), body mass index ( p = .006), and creatinine levels ( p = .007). Given the biochemical interaction of apoB and MTP proteins in the assembly of triglyceride-rich lipoproteins, we tested for their genetic interaction as a predictor of apoB concentration; T2D individuals with MTP T/T and apoB In/In had the highest apoB concentrations ( p = .05). MTP −493G/T was associated with nephropathy at follow-up ( p = .048), with G-allele homozygotes more likely to have nephropathy than T-allele carriers (odds ratio = 1.621, 95% confidence interval 1.004, 2.616). Conclusion: MTP −493G/T is associated with T2D and impacts lipoprotein parameters associated with complications in T2D. Importantly, we contribute novel evidence that lipoprotein metabolism genes are risk factors for diabetic complications.